BACTERIAL AND VIRAL DISEASES OF CROPS: DISTRIBUTION AND DIAGNOSTICS - A. N. Ignatov; S. V. Vinogradova; E. N. Goloveshkina; I. A. Zubareva (Овощи России, 2015)
A workshop devoted to «Problems of bacterial  and viral plant diseases  in agriculture and development of integrated  plant protection» was held at April; 24th 2013 at Russian University of People's  Friendship.